The utility of routine surveillance screening with magnetic resonance imaging to detect tumor recurrence/progression in children with high‐grade central nervous system tumors: a systematic review. Issue 2 (8th November 2018) - Stevens, Simon P.; Main, Caroline; Bailey, Simon; Pizer, Barry; English, Martin; Phillips, Bob; Peet, Andrew; Avula, Shivaram; Wilne, Sophie; Wheatley, Keith; Kearns, Pamela R.; Wilson, Jayne S.
Abstract: Background: Surveillance magnetic resonance imaging (MRI) is routinely used to detect recurrence in children with high‐grade central nervous system (CNS) tumors, although no consensus has been reached regarding its effectiveness and whether earlier detection is associated with improved patient outcomes. This review aimed to evaluate this practice and any associated benefits and harms. Methods: Systematic searches for relevant studies were undertaken in a number of databases, including MEDLINE and EMBASE, from 1985 to August 2018. Study selection and data extraction was undertaken independently by two reviewers. Due to heterogeneity between studies, no pooling of data was undertaken. Reporting followed Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Results: No comparative studies were identified. Three retrospective observational studies involving 306 patients were reviewed. All had high risk of bias by virtue of study design. Two studies reported outcomes by symptomatic status—both recurrence rates and overall survival for asymptomatic patients were comparable with those for clinically symptomatic patients. No quality‐of‐life outcomes were reported. Conclusion: There is a paucity of evidence to guide clinical practice as to the effectiveness of MRI surveillance in pediatric patients with high‐grade CNS tumors. These studies do not clearly demonstrate benefit or harm for the practice. With more research needed, there is a role for researchers to build into future trials data collection on surveillance imaging to give more information for the assessment of imaging frequency and duration in asymptomatic patients. This is an important question not only to clinicians and patients and their families but also from a health service resource perspective.